2016
DOI: 10.3390/polym8060212
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Biological Evaluation of Poly(Glutamic Acid)-b-Polyphenylalanine Polymersomes

Abstract: Different types of amphiphilic macromolecular structures have been developed within recent decades to prepare the polymer particles considered as drug delivery systems. In the present research the series of amphiphilic block-copolymers containing poly(glutamatic acid) as hydrophilic, and polyphenylalanine as hydrophobic blocks was synthesized and characterized. Molecular weights for homo-and copolymers were determined by gel-permeation chromatography (GPC) and amino acid analysis, respectively. The copolymers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…The THF used as eluent for size exclusion chromatography (SEC) analysis was of HPLC grade and purchased from Merck (Darmstadt, Germany). PGlu was synthesized in IMC RAS via the ring-opening polymerization of γ-O-benzyl-α-glutamic acid N-carboxyanhydride, and then deprotected with TFA/TFSA, as described elsewhere [32,33]. The characteristics of PGlu were the following: M w = 2100 (weight average molecular weight), M n = 2000 (number average molecular weight), Ɖ = 1.05 (dispersity), and the amount of residual benzyl groups was 22% (according to NMR) [34].…”
Section: Methodsmentioning
confidence: 99%
“…The THF used as eluent for size exclusion chromatography (SEC) analysis was of HPLC grade and purchased from Merck (Darmstadt, Germany). PGlu was synthesized in IMC RAS via the ring-opening polymerization of γ-O-benzyl-α-glutamic acid N-carboxyanhydride, and then deprotected with TFA/TFSA, as described elsewhere [32,33]. The characteristics of PGlu were the following: M w = 2100 (weight average molecular weight), M n = 2000 (number average molecular weight), Ɖ = 1.05 (dispersity), and the amount of residual benzyl groups was 22% (according to NMR) [34].…”
Section: Methodsmentioning
confidence: 99%
“…Recently it was observed that nanoparticles based on PGlu- b -PPhe copolymer did not affect cell metabolic activity 31 that clearly points to the poly(amino acid) nanoparticles biocompatibility. It is reasonable to suppose that the PGlu- b -PLeu particles are not cytotoxic as well.…”
Section: Resultsmentioning
confidence: 98%
“…The colloids obtained were then characterized by DLS method for measurement of hydrodynamic diameter of the prepared nanoobjects. TEM images was carried out as described in literature 31 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a new type of synthetic thin-shell structure, polymersomes self-assemble into vesicular structures based on amphiphilic block copolymers [12][13][14]. Compared with liposomes, polymersomes exhibit excellent stability and high membrane stability, and are promising alternatives to phospholipid-based vesicles [15][16][17][18].Furthermore, due to the difference in acidity between solid tumors and surrounding normal tissues, pH-responsive polymersomes have been widely noticed and studied, and their great potential in more e cient delivery and rapid drug release in tumor cells has been described.…”
Section: Introductionmentioning
confidence: 99%